A REVIEW ON INTELLIGENT COMPUTING TECHNIQUES ON MEDICAL IMAGE SEGMENTATION AND ANALYSIS - Pooja, Dr. Reena; Pooja, Dr. Reena (Chelonian Research Foundation, 2025)
A review of the idea of correcting for intensity inhomogeneity in magnetic resonance imaging is presented in this work. The information term in our variety system truly ensures the gradually shifting property of the inclination field obtained from the proposed vitality, without imposing an express smoothing term on the predisposition field. It evaluates the performance of a few selected MR images and provides the useful results with division and vitality advancement. This makes use of the level set technique, specifically for MR images, for synchronous division and inclination correction. Entropy is a crucial parameter that can be altered by adjusting the knots. MATLAB will be used for all of the simulations.